Combined UASB reactor and DAF/BF/anoxic/aerobic process for the removal of high-concentration organic matter and nutrients from slurry-type swine waste - Kim, B U (Water science and technology : a journal of the International Association on Water Pollution Research, 2004)
This research aimed to effectively remove high-concentration organic matter and nutrients from slurry-type swine waste using a combined upflow anaerobic sludge blanket reactor with the dissolved air flotation/aerobic submerged biofilm/anoxic/aerobic process. The upflow anaerobic sludge blanket reactor was operated at an organics volumetric loading rate of 3.2-6.1 kg COD/m3/day, and the removal rates of COD were 53.9-65.5%. The removal rate of COD of the overall process was more than 99%. In the aerobic submerged biofilm, over 95% of ammonium nitrogen was removed at a volumetric loading rate of 0.08-0.16 kg NH4+-N/m3/day. The specific denitrification rate was 0.257 g NO3-N/g MLVSS/day and the removal rate of total nitrogen was 86.7%. Phosphorus was removed by flocculation in the dissolved air flotation process, and 0.16 g of PO4-P was removed by 1 g of ferric ion